Membangun Motivasi Belajar melalui Lingkungan Sekolah yang Nyaman di Sekolah Dasar - Seprie Seprie (PTK: Jurnal Tindakan Kelas, 2025)
The majority of SDN 01 Maospati students stated that the spatial layout used was felt to be very supportive of their learning activities, so that every day they felt comfortable with their school environment. Uncomfortable school conditions result in decreased motivation to learn. The purpose of this study is to find out and analyze the influence of the school environment on the motivation of SDN 01 Maospati students. This research method is quantitative using linear regression analysis techniques through data collection with questionnaires on the entire student population of 85 children. The results of the study show that there is a positive and significant influence of the school environment on student learning motivation at SDN 01 Maospati, but in the assessment of student perception of the school environment as a means of learning and the value of student learning motivation is still in the medium category. The results of the learning motivation assessment in this study are strongly supported by the school environment as the main factor because it has a positive and significant influence.